Accurate Identification of Point-on-Wave Inception and Recovery Instants of Voltage Sags and Swells - Grazia Todeschini (IEEE Transactions on Power Delivery, 2018)
Voltage sags and swells are power quality events commonly observed in power systems; however, none of the existing methods allows determining their point-on-wave inception and recovery instants (and consequently, their duration) accurately in all cases. The primary goal of this paper is to determine these instants with little or no delay, by calculating the absolute rms voltage difference between two adjacent sliding windows. The proposed method is based on the assumption that this difference is maximum when the sample under analysis corresponds to either the inception or the recovery instant. This method is valid for both sag and swell events, with or without transients. Evaluation of the proposed method performance for different types of events shows that it is robust and highly accurate in determining the inception and recovery instants. The estimation error for the majority of the events analyzed is either 0 or 1 sample (each sample corresponds to a phase-angle difference of 2.81°), while the worst performance is 3 samples.